Coronary stent migration to aorta with successful recovery during aortobifemoral bypass - Jonathan P. Kerr, BS, ADN; Benjamin A. Greif, MD; Gregory G. Salzler, MD; Evan J. Ryer, MD; Robert P. Garvin, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
We present with full and proper consent of the patient, the case of a 64-year-old man with severe peripheral arterial disease and a known chronic infrarenal aortic occlusion causing severe short-distance claudication. Preoperative computed tomography angiography was significant for a new “cylindrical” calcified lesion. During the elective surgery, the lesion was confirmed to be a coronary stent. The coronary stent was confirmed to be from the patient's prior percutaneous coronary intervention to the left anterior descending artery 1 year prior. The stent was removed without complications by the surgical team. To the best of our knowledge, this is the first such case to be described in current literature. This patient is currently alive, and a revision of his left anterior descending artery intervention was found to be unwarranted on repeat coronary angiography.